Temperature measurement and control system for transtibial prostheses: Functional evaluation. - Ghoseiri, Kamiar; Zheng, Yong Ping; Leung, Aaron K. L.; Rahgozar, Mehdi; Aminian, Gholamreza; Lee, Tat Hing; Safari, Mohammad Reza (Assistive Technology, 2018)
The accumulation of heat inside the prosthetic socket increases skin temperature and fosters perspira- tion, which consequently leads to high tissue stress, friction blister, discomfort, unpleasant odor, and decreased prosthesis suspension and use. In the present study, the prototype of a temperature measurement and control (TM&C) system was designed, fabricated, and functionally evaluated in a phantom model of the transtibial prosthetic socket. The TM&C system was comprised of 12 thermistors divided equally into two groups that arranged internal and external to a prosthetic silicone liner. Its control system was programmed to select the required heating or cooling function of a thermal pump to provide thermal equilibrium based on the amount of temperature difference from a defined set temperature, or the amount of difference between the mean temperature recorded by inside and outside thermistors. A thin layer of aluminum was used for thermal conduction between the thermal pump and different sites around the silicone liner. The results showed functionality of the TM&C system for thermoregulation inside the prosthetic socket. However, enhancing the structure of this TM&C system, increasing its thermal power, and decreasing its weight and cost are main priorities before further development.